PERFORMANCE MEASUREMENT AND ANALYSIS OF COFFEE SUPPLY CHAIN WITH SCOR METHOD (CASE STUDY OF NORTH SUMATERA COFFEE) - PRASETYA, WIBAWA; NATALIA, CHRISTINE; KRISTIANA, STEFANI PRIMA DIAS; ELNATH ALDI, BENEDIKTUS; SILALAHI, AGUSTINUS; MONIQUE, KESHA; OKTAVIA, CHENDRASARI WAHYU (IJRDO - Journal of Business Management, 2017)
Coffee is the one of the commodities that push the economy of Indonesia. Almost all provinces have coffee plantations. North Sumatera is one of the 10th largest coffee producer in Indonesia, especially Dairi, Humbang Hasundutan, and North Tapanuli district. But the reality coffee plantation is unstable year by year and cause the farmers move to plant other commodities, such as orange and horticulture agriculture. This study measured performance of North Sumatera Coffee supply chain with SCOR method to overcome the problem in supply chain. The measurement is performed with several stage: SCOR matrix identification, Key Perfomance Identification (KPI) identification, normalixation score, and KPI weighting using Analytical Hirerchy Process (AHP) method. The result show that the score of supply chain performance is 48.224 with marginal category with the lowest final value is in delivery business process. This process can be improved by means of upgraded the quality of delivery products, required and shipped quantities must be the same, on time delivery of raw materials.